NADB-Reports : National Archaeological Database - USA - National Park Service; University of Arkansas (2007)
[Dt.:] Bibliographischer Nachweis von ca. 350.000 Berichten zur archäologischen Forschung in den USA. Überwiegend Graue Literatur, das heißt, nicht publiziert, nicht in bibliographischen Katalogen erfasst und zumeist in begrenztem Umlauf. - [Engl.:] Expanded bibliographic inventory of over 350,000 reports on archeological investigation in the USA. This "gray literature" is not published, not recorded in bibliographical catalogues and mostly of limited circulation.